The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.633502
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Endornaviruses Co-infecting a Phytophthora Pathogen of Asparagus officinalis Modulate the Developmental Stages and Fungicide Sensitivities of the Host Oomycete

Abstract: Two novel endornaviruses, Phytophthora endornavirus 2 (PEV2) and Phytophthora endornavirus 3 (PEV3) were found in isolates of a Phytophthora pathogen of asparagus collected in Japan. A molecular phylogenetic analysis indicated that PEV2 and PEV3 belong to the genus Alphaendornavirus. The PEV2 and PEV3 genomes consist of 14,345 and 13,810 bp, and they contain single open reading frames of 4,640 and 4,603 codons, respectively. Their polyproteins contain the conserved domains of an RNA helicase, a UDP-glycosyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 67 publications
0
18
1
Order By: Relevance
“…Recent studies have found that plants infected by Bell pepper endornavirus (BPEV) have alterations of organelles and other cell components, which are believed to be caused by parasitic effects between the endornavirus and host [ 53 ]. Additionally, the coinfection of Phytophthora endornavirus 2 (PEV2) and Phytophthora endornavirus 3 (PEV3) also affects the sensitivity of oomycetes to fungicides [ 54 ]. Here, we found that the SsEV11-infecting strain XY79 has some abnormal phenotypes, such as lower growth rate on PDA medium, delayed sclerotial formation and maturation, and decreased virulence on detached rapeseed leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that plants infected by Bell pepper endornavirus (BPEV) have alterations of organelles and other cell components, which are believed to be caused by parasitic effects between the endornavirus and host [ 53 ]. Additionally, the coinfection of Phytophthora endornavirus 2 (PEV2) and Phytophthora endornavirus 3 (PEV3) also affects the sensitivity of oomycetes to fungicides [ 54 ]. Here, we found that the SsEV11-infecting strain XY79 has some abnormal phenotypes, such as lower growth rate on PDA medium, delayed sclerotial formation and maturation, and decreased virulence on detached rapeseed leaves.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other viruses have been found in Phytophthora spp. [9][10][11][12][13][14]. Similar to Phytophthora, oomycete viruses were found in the Pythium and downy mildew [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 80%
“…Co-infection of Penicillium digitatum polymycovirus 1 and Penicillium digitatum narna-like virus 1 can reduce the fungicide resistance of Penicillium digitatum ( Niu et al, 2018 ). Persistent infection with Phytophthora endornavirus 2 and Phytophthora endornavirus 3 may impact the fungicide sensitivity of the host oomycete ( Uchida et al, 2021 ). The well-studied Sclerotinia sclerotiorum hypovirulence-associated DNA virus 1 (SsHADV-1) can convert its host ( Sclerotinia sclerotiorum ) from a typical necrotrophic pathogen to a beneficial endophytic fungus ( Yu et al, 2013 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%